Respuesta :
f(x) = (x-4)(x-3)
if you put x=4, it makes f(x) 0. if you put x=3 it makes f(x) 0
if you put x=4, it makes f(x) 0. if you put x=3 it makes f(x) 0
The quadratic function f whose zeros are 4 and 3 is [tex]\rm f(x) = x^2-7x+12[/tex] and this can be determined by using the given data.
Given :
Quadratic function f whose zeros are 4 and 3.
The following steps can be used in order to determine the quadratic function f whose zeros are 4 and 3:
Step 1 - The generalized quadratic equation is given by:
f(x) = (x - a)(x - b) --- (1)
Step 2 - According to the given data, quadratic function f whose zeros are 4 and 3.
Step 3 - Now, substitute the values of the known terms in the expression (1).
f(x) = (x - 4)(x - 3)
Step 4 - Simplify the above expression.
[tex]\rm f(x) = x^2-3x-4x+12[/tex]
[tex]\rm f(x) = x^2-7x+12[/tex]
For more information, refer to the link given below:
https://brainly.com/question/2263981